Penerapan Metode Kartu Make and Match terhadap Hasil Belajar Matematika pada Materi Bangun Ruang - Nurul Malikah; Lilis Dita Widhiasti (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2019)
Learning mathematics requires understanding, precision and exercises. It's just that the teacher lacks mastery of the situations and conditions of students in the process of learning mathematics. The study discusses the application of the Make and Match method to improve Mathematics Learning Outcomes in Space Building Materials for Class III Students at SDIT Darussalam Joresan Mlarak Ponorogo 2018/2019. Quantitative methods determine grade 3 of SDIT Darussalam Joresan Mlarak Ponorogo research sample analyzed using Product moment based on distributed tests. Mathematics learning outcomes 75.5% through the application of the make and match card method.